2018
DOI: 10.1074/jbc.ra118.004043
|View full text |Cite
|
Sign up to set email alerts
|

The rational design of affinity-attenuated OmCI for the purification of complement C5

Abstract: Complement component C5 is the target of the mAb eculizumab and is the focus of a sustained drug discovery effort to prevent complement-induced inflammation in a range of autoimmune diseases. The immune evasion protein OmCI binds to and potently inactivates C5; this tight-binding interaction can be exploited to affinity-purify C5 protein from serum, offering a vastly simplified protocol compared with existing methods. However, breaking the high-affinity interaction requires conditions that risk denaturing or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Ninety-six-well ELISA plates (Nunc Maxisorp) were coated with a 2 μg/mL solution of C5, purified from serum as previously described [ 47 ], in carbonate-bicarbonate buffer (Sigma). All washing steps comprised 4 wash cycles with PBS, 0.05% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety-six-well ELISA plates (Nunc Maxisorp) were coated with a 2 μg/mL solution of C5, purified from serum as previously described [ 47 ], in carbonate-bicarbonate buffer (Sigma). All washing steps comprised 4 wash cycles with PBS, 0.05% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…Using a Biacore 8K (GE Healthcare), C5 purified from serum [ 47 ] was immobilized on a CM5 chip by amine coupling. For PGT121 fusion proteins, flow cells were activated using a minimal immobilisation protocol: EDC/NHS was mixed at 1:2 ratio (flow rate, 10 μL/min; contact time, 30 s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement proteins. Human C5 was affinity purified using an E141A, H164A OmCI column (Macpherson et al, 2018). Briefly, human serum (TCS biosciences) was diluted 1:1 (v/v) with PBS, 20 mM EDTA and applied to a 5 mL Hi-Trap NHS column (GE Healthcare), which contained 20 mg of E141A H164A OmCI protein, at a rate of 1 mL/minute.…”
Section: Methodsmentioning
confidence: 99%
“…These inhibitors have K D values in the low nM range (Table 1). A recent study that used site-specific immobilization of OMCI and multicycle kinetics indicated that the K D may even be in the low pM ranges indicating that assay design can affect estimations of affinity (Macpherson et al, 2018). These inhibitors also show quite high expected concentrations at the feeding site, which is mostly due to their functioning as kratagonists (section below).…”
Section: Inhibitors That Target Sites Distant From Enzyme Active Sitesmentioning
confidence: 99%